TMOD-34. PATIENT-DERIVED XENOGRAFT AND CELL LINE MODELS FACILITATE NOVEL TREATMENT DISCOVERY IN CENTRAL NERVOUS SYSTEM LYMPHOMAS. (9th November 2020) - Meredith, David; Chow, Kin Hoe; Kao, Pei-Lun; Zeng, Yu; Sinha, Rileen; Shetty, Aniket; Tolstorukov, Michael; Tran, Tony; Yerrum, Smitha; Chukwueke, Ugonma; Bi, Wenya Linda; Arnaout, Omar; et al.
Abstract: Lymphomas of the central nervous system (CNSL) are rare tumors with few treatment options; however, recent genomic studies have uncovered several druggable targets. To facilitate novel treatment discovery, we sought to establish patient-derived xenograft (PDX) models and cell lines from patients with newly diagnosed or recurrent CNSL. PDX models were attempted from fresh tumor samples from 18 consented patients for whom rich clinical annotation was available. Orthotopic intracranial injections were performed via stereotactic injection. Cell line generation was attempted from both primary tumors (PDCL) and PDX samples (PDXCL). Characterization included histopathology, targeted exome sequencing, low-pass whole-genome sequencing for copy number evaluation, and expression profiling of matched patient tumors and PDXs. Drug response testing was performed using CellTiterGlo. From 18 samples attempted, 8 PDX models were successfully generated: 2 primary CNS diffuse large B-cell lymphoma (DLBCL), 5 secondary CNS DLBCL, and 1 secondary cutaneous T-cell lymphoma (CTCL). Mean time to moribund was 66 days. All 8 PDXs grew successfully as orthotopic models, and 4 also grew in subrenal capsule. Additionally, 6 PDCL and 2 PDXCL were established (> P3). Models faithfully represented primaries, showing nearly identical histopathology, immunoprofiles, and genomic signatures. To support expanded and rapid preclinical use of these models in drug testing we documented that PDX could be explanted to create short-term cell preparations or long-term cell lines with a 100% and 40% success rate, respectively. Proof of principle testing showed that explanted DLBCL PDX cells and cell lines showed sensitivity to copanlisib and venetoclax, which were not efficacious in the CTCL PDX. These findings showcase a diverse collection of CNSL models demonstrating high fidelity to primary tumors at the genomic and phenotypic levels, emphasizing their utility for preclinical studies and as patient avatars to rapidly determine sensitivities to existing and novel regimens prior to initiation of therapy.